Macro-anatomical investigations on the masticatory muscles of tree squirrel - Hakan Yalçın; Atilla Arslan; Sadettin Tıpırdamaz (Eurasian Journal of Veterinary Sciences)
In this study, adult squirrel (S. anomalus) were used 6 (5 male ve 3 female). The masticatory muscles (masseter. temporal, pterygoid, digastric, zygomaticomandibular muscles) were examined by the dissection. It was determined the superficial masseter originated from facial tubercle at the ventral to the infraorbital foramen and inserted to tuberculum on the lateral surface of the angular processs of the mandible. It was determined the anterior deep masseler orgmated from fossa on the lateral surface of the maxillary bone and inserted on the ventral masseteric ridge on the lateral surface of the mandible.